Structural connectivity of an interoception network in schizophrenia. (June 2023) - Yao, Beier; Gu, Pan; Lasagna, Carly A.; Peltier, Scott; Taylor, Stephan F.; Tso, Ivy F.; Thakkar, Katharine N.
Highlights: Interoception refers to the processing of bodily signals by the brain. Interoception is crucial to basic survival and cognition, especially emotion. Altered structural connectivity within an interoception network in schizophrenia. Network connectivity related with emotion recognition in healthy participants. Much weaker connectivity-emotion association in schizophrenia. Abstract: Interoception refers to the processing, integration, and interpretation of bodily signals by the brain. Interoception is key to not only basic survival, but also motivational and affective functioning. There is emerging evidence suggesting altered interoception in schizophrenia, but few studies have explored potential neural underpinnings. The current study aims to investigate the anatomical connectivity of a previously identified interoception network in individuals with schizophrenia, and the relationship between network structural connectivity and both emotional functioning and clinical symptoms. Thirty-five participants with schizophrenia (SZ) and 36 healthy control participants (HC) underwent diffusion tensor imaging (DTI) and performed tasks measuring emotional functioning. Probabilistic tractography was used to identify white matter tracts connecting key hubs in an interoception network. Microstructural integrity of these tracts was compared across groups and correlated with measures of emotional functioning and symptom severity. Compared with HC, SZ exhibited altered structural connectivity in the interoception network. In HC, the structural connectivity of the network was significantly correlated with emotion recognition, supporting a link between the interoception network and emotional functioning. However, this correlation was much weaker in SZ. These findings suggest that altered interoception may have implications for illness mechanisms of schizophrenia, especially in relation to emotional deficits.